FORMULASI ENUMERASI PADA MODEL JARINGAN INTERKONEKSI LUCAS-HYPERCUBE - Ernastuti, - (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2013)
Lucas-Hypercube (LH) is a new model of interconnection network topology that can be represented as a graph, where the set of vertices is constructed recursively as Hypercube network model with two sub graphs in which each of them is isomorphic to the Lucas cube, and the set of edges is built with the Hamming distance method. The research in this paper aims to prove that LH is classified in the network model of Fibonacci Cube family, by showing the parameter enumeration of the number of vertices and edges in the LH can be expressed as a unit function of the Fibonacci numbers. In this research, the relationship between the vertices, building formulations of enumerating the number of vertices and edges are analyzed through the lemmas and theorems that the whole approaches are performed with the combinatorial graph theory of binary strings. The analysis showed that the formulation of enumerating the number of vertices and edges can be expressed by the unit function of Fibonacci numbers respectively.